2002
DOI: 10.1034/j.1600-0676.2002.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin serum levels do not correlate with thrombocytopenia in hepatic schistosomiasis

Abstract: The results suggest that Tpo serum concentration does not mirror and/or has no significant participation in the mechanisms responsible for the thrombocytopenia observed in schistosomiasis patients with splenomegaly and portal hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…Portal hypertension in schistosomiasis may progress with variable degrees of pancytopenia, with thrombocytopenia as the main and earliest presentation. However, this thrombocytopenia is not explained by thrombopoietin serum concentrations (Souza et al. , 2002), which differs from that reported in severe forms of cirrhosis (Peck‐Radosavljevic et al.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Portal hypertension in schistosomiasis may progress with variable degrees of pancytopenia, with thrombocytopenia as the main and earliest presentation. However, this thrombocytopenia is not explained by thrombopoietin serum concentrations (Souza et al. , 2002), which differs from that reported in severe forms of cirrhosis (Peck‐Radosavljevic et al.…”
Section: Introductioncontrasting
confidence: 73%
“…Portal hypertension in schistosomiasis may progress with variable degrees of pancytopenia, with thrombocytopenia as the main and earliest presentation. However, this thrombocytopenia is not explained by thrombopoietin serum concentrations (Souza et al, 2002), which differs from that reported in severe forms of cirrhosis (Peck-Radosavljevic et al, 1997). The aim of the present study was to evaluate reticulated platelets and thrombopoietin serum levels in patients with chronic and isolated forms of schistosomiasis in order to better interpret the thrombocytopenia present in these patients.…”
Section: S U M M a R Ymentioning
confidence: 64%
“…For example, the blood of many, if not most, patients with myeloproliferative thrombocytosis display higher than expected TPO levels [15,16]. The same is true for reactive thrombocytosis associated with inflammation, or infection; the opposite is true for the thrombocytopenia of various states of liver disease, in which the hepatic source of TPO should be reduced, yet blood levels are occasionally higher than expected [8,9,17]. Several investigators have now demonstrated that marrow stromal cell production of TPO can rise in many of these states [18,19,20] and that the inflammatory mediator interleukin‐6 can increase TPO production from hepatocytes [21].…”
Section: The Regulation Of Thrombopoietin Productionmentioning
confidence: 99%
“…For the form without portal hypertension, lesion markers and hepatic function are within normal limits. Patients with portal hypertension are characterized by the extent of preservation of hepatic function in relation to the degree of portal hypertension, although some laboratory alterations have been found that characterize organ dysfunction from an early stage [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%